THE DIFFICULT BUSINESS OF BEING SOUND. SPACE, RHETORICS AND CARNNAL IN "THE ALIENIST" OFMACHADO DEASSIS - Fernandez, Camilo (2008)
In "TI1e Alienist", Machado de Assís recurs to orientational methaphor, to desmitificatingirony, and to carnivalization in arder to deal with madness in a way fit to questíon offícialknowledge, Thus, in his work, the borderline between madness and soundness is not clearbecause the madman and the wise have points ín common ín what it relates to knowledge.